2018
DOI: 10.3390/su10114127
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Method for Project Transaction Mode Design Based on Case-Based Reasoning: A Chinese Case Study

Abstract: Aiming at the design of a project transaction mode, the case-based reasoning (CBR) method is used as a methodology to build a case-based reasoning system based on project performance predictions. Thirty-four cases are initially selected for the practical application. Based on the classical CBR, the performance forecast is added, an improved continuous variable interpolation scoring method is proposed, and three types of manual revision methods are proposed: owner’s preference for the project transaction mode, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…They found that the weighted Mahalanobis distance may not be an effective distance measurement as compared to the Euclidean distance, but can still provide an acceptable estimation performance depending on the data conditions. Ding et al [51] proposed a model for the evaluation of project performance. In their research, three distance algorithms were employed for the measurement of the similarity distance depending on the types of attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that the weighted Mahalanobis distance may not be an effective distance measurement as compared to the Euclidean distance, but can still provide an acceptable estimation performance depending on the data conditions. Ding et al [51] proposed a model for the evaluation of project performance. In their research, three distance algorithms were employed for the measurement of the similarity distance depending on the types of attributes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This methodology is useful because it can be applied when relevant datasets are limited or inadequate, even if the problems are not well-organized [60,61]. CBR has been used in a variety of fields, such as cost estimation, safety diagnosis, maintenance, and duration estimation [37,40,51]. In general, CBR comprises four steps: Case retrieval, case reuse, case revision, and case retention [14,20,33,35].…”
Section: Similarity Distance Measurement With Cbrmentioning
confidence: 99%
See 2 more Smart Citations
“…The appropriate PPM could reduce project costs by an average of 5% [3]. The most common PPMs in the construction industry include Design Bid Build (DBB), Design Build (DB), Construction Management (CM), Engineering Procurement Construction (EPC), construction management as program management (CM) [4,5], and Public Private Partnership (PPP) [6,7]. Each form of PPM is unique and cannot be effectively applied to all projects because of their different characteristics [4,8].…”
Section: Introductionmentioning
confidence: 99%